Nanopriming with zinc oxide: a novel approach to enhance germination and antioxidant systems in amaranth - Geremew, Addisie; Stovall, Leandrea; Woldesenbet, Selamawit; Ma, Xingmao; Carson, Laura (Frontiers in Plant Science, 2025)
Germination is a complex physiological and biochemical process influenced by various factors, including metabolic activation and antioxidant defense mechanisms. This study investigated the effects of zinc oxide nanoparticles (ZnO NPs) of different sizes (ZnO10 and ZnO35) as seed priming agents on the germination, biochemical traits, and antioxidative systems of Amaranthus tricolor seeds. ZnO NPs were characterized by UV-Vis maximum peaks at 352 nm and 364 nm and average sizes of 10.0 nm and 35.2 nm for ZnO10 and ZnO35, respectively. Additionally, zeta potential indicated high stability, while transmission electron microscopy confirmed spherical morphology, energy dispersive X-ray showed high purity, and X-ray diffraction peaks indicated crystallinity. Germination percentage (GP) and germination rate (GR) were significantly improved by ZnO NP treatments, particularly at 400 mg/L, with ZnO10-primed seeds achieving 100% GP compared to 91.5% in ZnO35-primed seeds. Additionally, seedling vigor indices followed a similar trend, with ZnO10-primed seeds showing the highest vigor (2380) compared to ZnO35-primed seeds (1793.4). ZnO NPs significantly enhanced water uptake, with ZnO10 NPs demonstrating superior absorption at increasing concentrations, reaching a maximum of 93.6% at 400 mg/L. The α-amylase activity was also significantly higher in ZnO10-primed seeds (1.9 mg/g) than ZnO35-primed seeds (0.81 mg/g) at 400 mg/L suggesting enhanced enzymatic activation and metabolic efficiency. Antioxidant enzyme activities, including superoxide dismutase, catalase, peroxidase, ascorbate peroxidase, and glutathione peroxidase, were significantly enhanced in ZnO NP-primed seedlings, indicating improved oxidative stress management. Furthermore, lipid peroxidation, measured as malondialdehyde content, was significantly reduced, with ZnO10 NPs demonstrating an 89.3% reduction at 400 mg/L. The non-enzymatic antioxidant response was also enhanced, with total phenolic content and total flavonoid content significantly increased in ZnO NP-treated seedlings. The findings show that smaller-sized ZnO10 NPs enhance seed germination, biochemical activation, and antioxidative defense, improving seedling establishment. The high surface area of NPs enhances seed interaction and water uptake, and stimulates enzymatic activities, ultimately improving metabolic activation and protection against oxidative stress. ZnO NPs demonstrate strong potential as effective priming agents for A. tricolor.